Diagnostic and prognostic implications of 2018 guideline for the diagnosis of idiopathic pulmonary fibrosis in clinical practice - Jooae Choe (Nature Portfolio, 2021)
Abstract The purpose of this study was to evaluate the implications of the 2018 updated guideline for the diagnosis of idiopathic pulmonary fibrosis (IPF) in clinical practice compared to 2011 guideline. This study involved 535 patients including 339 IPF and 196 non-IPF, and we retrospectively evaluated CT classifications of usual interstitial pneumonia (UIP) by two guidelines. Interobserver agreement of 2018 criteria showed moderate reliability (κ = 0.53) comparable to 2011 (κ = 0.56) but interobserver agreement for probable UIP was fair (κ = 0.40). CT pattern of indeterminate for UIP was associated with better prognosis compared with the other groups (adjusted hazard ratio [HR] = 0.36, p < 0.001). Compared to possible UIP, probable UIP demonstrated a lower positive predictive value (PPV, 62.9% vs 65.8%). In analysis of patients with CT patterns of non-definite UIP, diagnosing IPF when CT pattern showed probable UIP with lymphocyte count ≤ 15% in BAL fluid, and either male sex or age ≥ 60 years showed a high specificity of 90.6% and a PPV of 80.8% in the validation cohort. The 2018 criteria provide better prognostic stratification than the 2011 in patients with possible UIP. BAL fluid analysis can improve the diagnostic certainty for IPF diagnosis in patients with probable UIP CT pattern.